2022
DOI: 10.1186/s12902-022-01214-0
|View full text |Cite
|
Sign up to set email alerts
|

Exploring facilitators and barriers to self-management engagement of Chinese people with type 2 diabetes mellitus and poor blood glucose control: a descriptive qualitative study

Abstract: Aims To explore facilitators and barriers to self-management engagement of Chinese people with poorly controlled type 2 diabetes. Methods Purposive sampling method was used for recruitment. Semi-structured interview and thematic analysis was used for data collection and analysis. Results Twenty-six semi-structured interviews were conducted. Poor blood glucose control introduced awareness of susceptibil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 64 publications
3
3
0
1
Order By: Relevance
“…Although both doctors and patients considered self-monitoring of blood glucose important, most patients rarely did this consistently [ 21 ]. Similar to the previous study, we also found that temporary improvements in glycaemic management could lead to discontinuity of medication use [ 22 ]. Health education activities organized by PHC facilities are an important mechanism to enhance patient awareness and knowledge of T2DM.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Although both doctors and patients considered self-monitoring of blood glucose important, most patients rarely did this consistently [ 21 ]. Similar to the previous study, we also found that temporary improvements in glycaemic management could lead to discontinuity of medication use [ 22 ]. Health education activities organized by PHC facilities are an important mechanism to enhance patient awareness and knowledge of T2DM.…”
Section: Discussionsupporting
confidence: 89%
“…Patients were most motivated to make a change when they felt ‘unwell’ and tended to not consider regular self-monitoring as a priority. Consistent with prior research, our findings highlight a limited awareness of the potential health harm and financial risks of diabetes complications, which in turn undermines patients’ motivation to actively participate in self-management [ 22 ]. Finally, patients tended to have a passive management relationship with care providers which undermines the effectiveness of various health interventions provided by the PHC facilities, a finding also consistent with previous studies [ 19 , 25 , 26 ].…”
Section: Discussionsupporting
confidence: 84%
“…This aligns with previous research emphasizing the influence of nihilistic attitude on health behaviours and chronic disease management [ 30 ]. In the current study the negative attitude toward diabetes self-care may be due to multifaceted factors such as cultural beliefs, socioeconomic challenges, availability of limited and equitable health care resources and psychological distress (diabetes related distress) [ 31 ]. Cultural influences often shape individuals’ perceptions of illness and death, impacting their approach to managing chronic conditions [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…[20] Similar to the previous study, we also found that temporary improvements in glycaemic management could lead to discontinuity of medication use. [21] Health education activities organized by PHC facilities are an important mechanism to enhance patient awareness and knowledge of T2DM. However, such activities tend to only reach people who are already aware of the importance and are less effective in reaching others.…”
Section: Discussionmentioning
confidence: 99%